Bunaji cattle at the Shika Research Station: North Central state, Nigeria - Wheat, J.D.; Leeuw, P.N. de; Koch, B.A. (1972)
Effects of sire, sex and month of birth on body weights of Bunaji, Friesian x Bunaji and Brahman x Bunaji crossbred cattle were investigated at Shika research station, Nigeria. Data on calving intervals included.